JORNALISMO NA COPA DO MUNDO 2014: OS INTERESSES POLÍTICOS E A INSTRUMENTALIZAÇÃO DA NOTÍCIA NOS JORNAIS FOLHA DE S.PAULO E O GLOBO - Reis, Rodrigo Nascimento (2017)
The master thesis investigates if the newspapers Folha de S. Paulo and O Globo instrumentalized the news about the 2014 World Cup in Brazil to defend political and economic interests. The study assumes that journalism has the ability to schedule issues in the society and form public opinion. The hypothesis is that these newspapers associated their publications with the electoral interests of certain politicians. The methodology includes bibliographical research and analysis of the journalistic content referring to the headlines on the front page of the two newspapers between May and July 2014. The research is guided by the Agenda-Setting Theory, McCombs (2009) and concepts of social actors and formation of public opinion in Habermas (2012a; 2012b). Among the results, there were 427 headlines in Folha de S. Paulo and 534 in O Globo, which scheduled, almost daily, the World Cup through news, editorials, reports, columns, articles and notes. In this way, the journalistic coverage could be organized by categories: championship, organization, political issues, protests and expenses with the event, besides having been mapped the presence of political actors. Thus, the issues regarding the World Cup with a focus on politics were analyzed from the perspective of Habermas, in which Folha de S. Paulo and O Globo maintained narratives with an interest coining a negative image of president Dilma Rousseff. Also the political actors listed in the narratives expressed private, political, economic and electoral interests around the World Cup